2010
DOI: 10.1080/10503301003705871
|View full text |Cite
|
Sign up to set email alerts
|

Clients', therapists', and observers' agreement on the amount, temporal location, and content of psychotherapeutic change and its relation to outcome

Abstract: Clients', therapists', and observers' identification of change was studied in 27 therapeutic processes, and agreement on the amount, temporal location, and content of change was related to outcome. Results show that clients reported more changes in successful therapies. Client-therapist temporal match of change moments was low irrespective of outcome. Results from all three perspectives were consistent in that manifestation of new behaviors and emotions was the most representative content of change among all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0
16

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 23 publications
3
30
0
16
Order By: Relevance
“…In order to do this, the study of Gómez (2016) integrates the knowledge obtained from previous research on psychotherapy and healing from sexual abuse considering the views of the victims (Banyard & Williams, 2007;Capella et al, 2016;Draucker et al, 2009Draucker et al, , 2011Foster & Hagedorn, 2014;Harvey et al, 2000;Jessiman et al, 2017;Nelson-Gardell, 2001;Phanichrat & Townshend, 2010;Phillips & Daniluk, 2004;Saha, Cheung, & Thorne, 2011) and the theoretical-clinical conceptualizations of psychotherapy in sexual abuse cases (Barudy, 1998;Cantón & Cortés, 2004, Capella & Gutierrez, 2014Gil, 2006;Llanos & Sinclair, 2001;Malacrea, 2000), complemented with the results of research on psychotherapeutic change (Altimir et al, 2010;Echá-varri, et al, 2009;Gonçalves et al, 2009;Krause, 2005;Krause et al, 2006) and psychotherapy with children and adolescents in the general clinical population (Binder, Moltu, Hummelsund, Sagen., & Holgersen, 2011;Bury, Raval, & Lyon, 2007;Carlberg, 1997;Carlberg et al, 2009;Caroll, 2002;Fernández, 2013;Gibson & Cartwright, 2014;Midgley, 2004;Midgley, Target, & Smith, 2006;Stith, Rosen, McCollum, Coleman, & Herman, 1996). From this point of view, Gómez (2016) suggests that psychotherape...…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to do this, the study of Gómez (2016) integrates the knowledge obtained from previous research on psychotherapy and healing from sexual abuse considering the views of the victims (Banyard & Williams, 2007;Capella et al, 2016;Draucker et al, 2009Draucker et al, , 2011Foster & Hagedorn, 2014;Harvey et al, 2000;Jessiman et al, 2017;Nelson-Gardell, 2001;Phanichrat & Townshend, 2010;Phillips & Daniluk, 2004;Saha, Cheung, & Thorne, 2011) and the theoretical-clinical conceptualizations of psychotherapy in sexual abuse cases (Barudy, 1998;Cantón & Cortés, 2004, Capella & Gutierrez, 2014Gil, 2006;Llanos & Sinclair, 2001;Malacrea, 2000), complemented with the results of research on psychotherapeutic change (Altimir et al, 2010;Echá-varri, et al, 2009;Gonçalves et al, 2009;Krause, 2005;Krause et al, 2006) and psychotherapy with children and adolescents in the general clinical population (Binder, Moltu, Hummelsund, Sagen., & Holgersen, 2011;Bury, Raval, & Lyon, 2007;Carlberg, 1997;Carlberg et al, 2009;Caroll, 2002;Fernández, 2013;Gibson & Cartwright, 2014;Midgley, 2004;Midgley, Target, & Smith, 2006;Stith, Rosen, McCollum, Coleman, & Herman, 1996). From this point of view, Gómez (2016) suggests that psychotherape...…”
mentioning
confidence: 99%
“…Considering children and adolescents' perspectives during the psychotherapy is relevant because it has been observed that psychotherapy in general, and specifically in these cases, involves several moments that possess differential characteristics Altimir et al, 2010;Echávarri et al, 2009;Gonçalves et al, 2009). Therefore, research that inquiries into participants' views only during the final phase of therapy could be losing their perspectives during the psychotherapy, which may well differ from their final opinion and serve to inform treatment at multiple stages of the process.…”
mentioning
confidence: 99%
“…Dentro del paradigma de los eventos, la trayectoria de investigación más extensa y prolífica se abocó a los episodios de cambio (Altimir et al, 2010;bastine et al, 1989;Elliott, 1984;Krause, et al, 2006Krause, et al, , 2007. más recientemente, la investigación en el campo se ha centrado en los episodios de estancamiento (Fernández et al, 2012;herrera, Fernández, Krause, Vilches, Valdés, & Dagnino, 2009) y en las rupturas de alianza y eventos de resolución (barros, Coutinho, Ribeiro, hill, & Safran, 2011;muran, Safran, Gorman, Samstag, Eubanks-Carter, & Winston, 2009;Safran, & Kraus, 2014).…”
Section: Eventos Significativos En Psicoterapiaunclassified
“…Notably, even when clients did not show quantitative change, clients attributed valuable changes to therapy qualitatively (Klein & Elliott, ). Finally, in a study examining outcomes from different perspectives (i.e., clients, therapists, trained observers), a significant positive association was found between qualitative and quantitative change (Altimir et al, ) from the client's point of view; no relationship was found between the two methods from the therapist or observer viewpoint. In summary, these studies suggest that while quantitative and qualitative outcomes converge at the extremes, such convergence is not evident overall, indicating the need for further mixed design outcome research.…”
Section: Introductionmentioning
confidence: 98%